2022
DOI: 10.3389/fnhum.2022.1074587
|View full text |Cite
|
Sign up to set email alerts
|

Difference analysis of multidimensional electroencephalogram characteristics between young and old patients with generalized anxiety disorder

Abstract: Growing evidences indicate that age plays an important role in the development of mental disorders, but few studies focus on the neuro mechanisms of generalized anxiety disorder (GAD) in different age groups. Therefore, this study attempts to reveal the neurodynamics of Young_GAD (patients with GAD under the age of 50) and Old_GAD (patients with GAD over 50 years old) through statistical analysis of multidimensional electroencephalogram (EEG) features and machine learning models. In this study, 10-min resting-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Previous studies have reported a clear correlation between EEG rhythms and alternate EEG features in GAD patients ( 60 ). Additionally, our previous research has pointed to the importance of beta rhythms in GAD ( 20 ).…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have reported a clear correlation between EEG rhythms and alternate EEG features in GAD patients ( 60 ). Additionally, our previous research has pointed to the importance of beta rhythms in GAD ( 20 ).…”
Section: Discussionmentioning
confidence: 80%
“…The functional organization of the brain determines its connectivity [ 39 ]. Recent research mentions that mental illnesses result from abnormal brain connectivity, where disruptions or even interruptions in the functional structure of the brain lead to disorders such as DD and GAD [ 11 , 17 ]. Brain functional reorganization is closely associated with abnormalities in brain functional connections [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the brain functional reorganization in GAD patients involves alterations in both the number [ 21 ] and the strength of connections [ 13 ]. The abnormal activation in the high-frequency beta band is indicative of anxiety manifestations in both DD and GAD [ 11 , 17 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The histological and molecular differences in generating protein between young and old hens were explored in the present study, which has been demonstrated as a critical way to reveal the targets for regulating albumen quality ( Wang et al, 2022 ). In the current study, albumen quality, magnum tissue and physiological conditions were analyzed and compared between 40- and 100-week-old hens.…”
Section: Introductionmentioning
confidence: 99%